Atopic dermatitis in preterm infants. - Mazzotta, F.; Ottomano, L.; Mautone, A.; Limoli, O.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
250 preterm and 250 at term infants who were consecutively born in the Neonatal Unit of Bari University were invited by letter to a control visit, aimed to investigate the prevalence of atopic diseases in this group. A personal and family history for atopic diseases and a careful dermatological and pediatric examination were performed in the 119 preterm and 104 at term children who came to the control visit. Atopic dermatitis was less frequent (5%) in preterm as compared with at term (13,5%) babies.